2009
DOI: 10.1007/s11547-009-0461-z
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction at work among radiologists

Abstract: This pilot study identified the sources of professional satisfaction and dissatisfaction among radiologists. A future survey of a stratified random sample of Italian radiologists appears to be feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
(80 reference statements)
1
15
0
Order By: Relevance
“…More than half of all radiation workers felt total dissatisfaction. Consistent with our study, Magnavita et al (11) declared that only 49% of diagnostic radiologists were satisfied with their jobs. Another study among oncology staff in radiation oncology departments in New Zealand found a high level of job satisfaction (3.75 mean score out of 5) (12).…”
Section: Discussionsupporting
confidence: 92%
“…More than half of all radiation workers felt total dissatisfaction. Consistent with our study, Magnavita et al (11) declared that only 49% of diagnostic radiologists were satisfied with their jobs. Another study among oncology staff in radiation oncology departments in New Zealand found a high level of job satisfaction (3.75 mean score out of 5) (12).…”
Section: Discussionsupporting
confidence: 92%
“…In terms of supplementary evidence of the scale's two-factor consistency, however, past findings have been limited. Magnavita, Fileni, and Bergamaschi (2009) demonstrated a two-factor solution via principal components analysis with an Italian translation of the scale, although the solution did not exactly mirror the items loadings in Warr et al's original intrinsic/extrinsic factor solution. Short forms of the scale, such as the eight-item variant by Dorman and colleagues (Dormann, Fay, Zapf, & Frese, 2006;Dormann & Zapf, 2001) based on Warr et al's original measure, also appear to assume two-factor representativeness on the basis of the original exploratory findings yet do not provide evidence supporting this assumption.…”
Section: Structural Properties Of the Jssmentioning
confidence: 83%
“…In terms of supplementary evidence of the scale's two-factor consistency however, past findings have been limited. Magnavita, Fileni, and Bergamaschi (2009) (Dormann, Fay, Zapf, & Frese, 2006;Dormann & Zapf, 2001) based on Warr et al's original measure, also appear to assume two-factor representativeness on the basis of the original exploratory findings, yet do not provide evidence supporting this assumption. In summary, evidence for the two factor solution is primarily exploratory in quality, and of limited consistency.…”
Section: Structural Properties Of the Jssmentioning
confidence: 87%
“…In fact, the specific characteristics required for diagnosis by imaging, the limited patient contact (and subsequent reduced social support), high degree of responsibility, and workload that cannot be managed by the person involved, provide a rational explanation for the “strain” measured by DCS model, while the disparity between the high degree of professional commitment and the static nature of material and immaterial rewards offered by the health service in subjects who are naturally prone to professional overcommitment explains the change in stress scores measured by the ERI model. Previous studies have identified specific stressors in the work of radiologists and radiotherapists [2833] and have shown that the latter often derive little satisfaction from their job [31, 34]. …”
Section: Discussionmentioning
confidence: 99%